Refill Station as a Strategy in Promoting Environmental Sustainability : Strategic Communication by The Body Shop Indonesia - Pradipta, Fransisca Diva Ayu; Praharsiwi, Caecilia Santi (Jogjakarta Communication Conference (JCC), 2024)
The development of the beauty industry cannot be separated from environmental issues. Since, most of the waste in Indonesia comes from cosmetic packaging. Cosmetic companies need to respond to this problem and promote environmental sustainability. However, companies need to involve consumers to get more significant results and raise awareness among the wider community. The Body Shop Indonesia initiated this collective action that involves consumers through the Refill Station Program. Our research used a case study approach and applied a strategy communication for sustainable development model to see how The Body Shop Indonesia promotes environmental sustainability in the Refill Station program. The results of the study show that collective action can be an innovative strategy in resolving environmental issues. The company carried out this innovation by involving external stakeholders from the problem identification process through program execution. By involving external stakeholders from the beginning, companies can create effective programs and encourage public engagement.